Root-Induced Iron Oxidation and pH Changes in the Lowland Rice Rhizosphere - Begg, C. B. M.; Kirk, G.J.D.; Mackenzie, A.F.; Neue, H.U. (Wiley, 1994)
Measurements of profiles of ferrous and ferric iron and pH in blocks of reduced soil in contact with planar layers of rice (Oryza sativa L.) roots are reported. Initially 11‐d‐old plants were kept in contact with the soil for up to 12 d. Over this period, substantial quantities of iron were transferred towards the root plane, producing a well‐defined zone of ferric hydroxide accumulation. The pH in this zone fell by more than two units. The profiles changed with time. The decrease in pH was in part due to protons generated in ferrous iron oxidation, and in part due to protons released from the roots to balance excess intake of cations over anions, N being taken up chiefly as NH4+. But the decrease in pH was less than expected from the net acid production in these two processes, possibly because of proton consumption in CO2 uptake by the roots. Because of the pH‐dependence of soil acidity diffusion, the two sources of acidity greatly reinforce each other. Some implications for nutrient and toxin dynamics are discussed.